Inclusion of Solvent Extracted Karanj (Pongamia glabra) Cake in the Diet and Production Performance of Layer Chicken - Raju, M.V.L.N.; Prakash, B.; Nagarjuna, B.V. R.; Nischala, T.; Rao, S.V. Rama; Reddy, M. R.; Panda, A. K. (Indian Journal of Animal Nutrition, 2018)
A total of 160 White Leghorn laying chicken (Lohmann) of 50 weeks of age were divided into four groups having 10 replicates of 4 chicken in each group. Solvent extracted karanj (Pongamia glabra) cake (SKC) was included in the diet at graded levels (0, 6, 9 and 12%) on iso-nitrogenous and iso-caloric basis and fed to the treatment groups from 50 to 61 weeks (3 laying periods of 4 weeks each) ad lib. The egg production and egg mass decreased (P<0.01) with SKC at 12% whereas feed intake decreased at 9 and 12% SKC in diet. However, feed intake per 12 eggs, egg weight and serum biochemical profile (except alkaline phosphatase activity which was lower in SKC fed groups) were not affected by the dietary SKC levels. The inclusion of SKC up to 12% in layer diet did not affect the quality and sensory attributes of eggs. It was concluded that SKC could be used up to 9% in the diet of laying chickens without any adverse effect while there was a decline in production at inclusion level of 12% SKC in diet.